Hard heads, soft hearts : a new reform agenda for Australia - Kelly, Paul, 1947-; Dawkins, Peter J. (Crows Nest, N.S.W. : Allen & Unwin, 2003)
A bold contemporary statement for an economic and social reform agenda, this title draws on contributions from a wide range of Australia's leading thinkers across academia, politics, the Public Service, business, unions and community groups.
Includes index.
Bibliography; p. [213]-224.
Keywords: Australia -- Economic policy -- 2001-; Australia -- Social conditions -- 2001-; Australia -- Economic conditions -- 2001-; Australia -- Social policy -- 2001-